Sub‐5 nm Patterning by Directed Self‐Assembly of Oligo(Dimethylsiloxane) Liquid Crystal Thin Films. Issue 45 (30th September 2016) - Nickmans, Koen; Murphy, Jeffrey N.; de Waal, Bas; Leclère, Philippe; Doise, Jan; Gronheid, Roel; Broer, Dick J.; Schenning, Albertus P. H. J.
Abstract : Highly ordered nanopatterns are obtained at sub‐5 nm periodicities by the graphoepitaxial directed self‐assembly of monodisperse, oligo(dimethylsiloxane) liquid crystals. These hybrid organic/inorganic liquid crystals are of high interest for nanopatterning applications due to the combination of their ultrasmall feature sizes and their ability to be directed into highly ordered domains without additional annealing.